Heroes of baseball : the men who made it America's favorite game - Lipsyte, Robert (Atheneum Books for Young Readers, 2005)
Presents a collection of illustrated stories about the men who help popularize and immortalize the sport of baseball, from Ty Cobb and Shoeless Joe Jackson to Mickey Mantle and Willie Mays and more.